Critical Discourse Analysis: Papuan Rejection of the Free Nutritious Food Policy - Iwan Joko Prasetyo; Nur'annafi Farni Syam Maella; Nevrettia Christantyawati; Didik Sugeng Widiarto (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
This research analyzes the media discourse construction regarding the rejection of the free nutritious meal program (MBG) policy by Papuan students through the Critical Discourse Analysis (CDA) approach using Teun A. Van Dijk's social cognition model. The focus of the research is directed toward a news article from Tempo.co titled